Internet mediation and the family gap: explorative ethnographic interviews in new family forms in Belgium. Issue 4 (1st October 2016) - Mostmans, Lien
Abstract: While studies have examined how parents organize, manage, or mediate children's internet use, perspectives of non-traditional, new forms of family remain largely neglected in the research. Presenting the initial findings of explorative ethnographic work within one multi-household stepfamily and one divorced one-parent household in Belgium, this article points to the challenges of internet mediation in new family forms as it involves complex interpersonal dynamics that are the result of major changes in family life, and the fact that parenting is distributed between parents in different households with their own media use norms. Specifically, this study found that children in multi-household families experience different mediation regimes and navigate relatively easily between them, but also that post-divorce family life can generate dynamics that mitigate the outcomes of parental mediation, as well as intensify the role of peer-siblings in internet mediation. Methodological implications and suggestions for future family media research are discussed.